Fresh-Keeping Effort and Channel Performance in a Fresh Product Supply Chain with Loss-Averse Consumers’ Returns - Bojun Gu (Mathematical Problems in Engineering, 2018)
We consider a fresh product supply chain consisting of one fresh product supplier and one e-tailer. Supplier sells fresh products through e-tailer in an online market, and the e-tailer offers a full-refund return policy to loss-averse consumers and exerts a fresh-keeping effort to keep the product at the optimum freshness level. By developing an analytical model, we derive the optimal price, quantity, and fresh-keeping effort jointly and verify that it is unique in the centralized setting. Based on the comparison, we demonstrate that the e-tailer’s profit is greater with fresh-keeping effort than without it; therefore, the e-tailer has an incentive to engage in fresh-keeping effort. We also show that the return rate is independent of the fresh-keeping effort and consumers’ loss aversion. In the decentralized setting, we first characterize the optimal wholesale price by the numerical study and then find that although the buyback contract still works, the revenue-sharing contract fails to achieve channel coordination under our model formulation. Furthermore, we develop a revenue- and cost-sharing contract that can coordinate the supply chain by designing a new contractual mechanism. Our numerical studies offer the Pareto improvement regions under the buyback and revenue- and cost-sharing contracts in which the supplier and e-tailer can earn more expected profits compared with being under wholesale price contract.